Adaptation and psychometric analysis of the Emotional Intelligence View Nowack’s (EIV) questionnaire in the Portuguese context - Candeias,Adelinda Araújo (2021)
Abstract During the last two decades, several studies have demonstrated the usefulness of emotional intelligence (EI) to understand job performance, job satisfaction, and well-being and quality of life (Nowack, 2006, 2014). This study analyzes the psychometric properties of the Emotional Intelligence View (EIV) in the Portuguese population. Participants were 708 professionals working in different job sectors (banking, management, and health) from the whole country. The EIV is a self-report scale composed of 74 items assessing emotional intelligence in organizations. It is organized in five dimensions: General EI competence, self-management, adaptability, relationship management, and leadership. The results showed that EIV presents a coherent factor structure. Results pointed to differences between men and women concerning leadership and emotional self-management. Positive correlations were found between age and educational level. It is concluded that EIV is a valid and reliable measure to evaluate EI in professionals working in different job sectors.